Keefektifan Steinernema Spp. Terhadap Spodoptera Exigua : Effectiveness Of Steinernema Spp. Against Spodoptera Exigua - Perpustakaan UGM, i-lib ([Yogyakarta] : Master of Management Program UGM, 2003)
Abstract: Effectiveness of entomopathogenic nematodes Steinernema spp. against mortality of larvae and pupae of Spodoptera exigua Hubner (Lepidoptera: Noctuidae) was evaluated in the Laboratory of Nematology and Biological Control at the Faculty of Agriculture, Gadjah Mada University. The most virulent isolate of the nematode was selected amongst isolates _from Solo, Jombang, and Medan. The effectiveness was determined by analising mortality of the S. exigua that was treated with Steinernema spp. at concentration rates of 0, 50, 100, 200, 400 Infective Juvenil (1J) per 1.5 mL aquadest. Inoculation of the nematode was done by filter paper method. Results showed that all isolates were able to infect the third instar of S. exigua. Solo and Jombang isolates caused relative similar in mortalities ca. 98 and 94%, and significantly higher than Medan isolate ca. 86. Hence, the Solo isolate was preferred for efficacy against the insect larvae and pupae. The mortality of S. exigua due to the Steinernema spp. was influenced by the insect instars. The insect mortality-rates of L1, L2, and pupae were 13,3